Exploring job hopping behavior among managers of casual dining restaurants in Klang Valley Area, Malaysia - Ghazali, Hazrina; Mokhtar, Khairunnisa (Institute of Research and Journals, 2020)
The job hopping phenomenon has become problems to many organizations because employee job hop for various reasons. A large degree of employees’ job hopping may be detrimental to both the organization as well as the employees. Therefore management plays a significant role as organizations’ success is dependent on management's ability to retain valuable and talented employees. Employees tend to leave an organization that cannot match with their expectations and move to another organization through the availability of many options of the job vacancy. This crisis continues to represent one of the most significant challenges faced by the restaurant industry. The purpose of this study is to explore empirically managers’ views on factors that may lead to job-hopping behaviour in the casual dining restaurant. This qualitative study collected data from 10 managers of casual dining restaurant by using the semi-structured interview. Findings revealed three main reasons associated with job hopping behaviour that are career growth, financial and benefits and customers complaints. These findings provide a better understanding for restaurant operation and human resource management to view employees’ job hopping scenario and how the organization can control this job-hopping behaviour decision from occur. Previous research on job hopping mainly focuses on non-managerial employees’ perspective and this study is believed to be the first empirical research in Malaysia restaurant industry particularly in the casual dining typed of restaurant. Hopefully, this study will help the restaurant owners or operators to formulate effective strategies to retain employees from leaving the industry.